A Sensitive Method for Detecting Zika Virus Antigen in Patients' Whole-Blood Specimens as an Alternative Diagnostic Approach. (6th June 2017) - Lum, Fok-Moon; Lin, Cui; Susova, Olga Y; Teo, Teck-Hui; Fong, Siew-Wai; Mak, Tze-Minn; Lee, Linda Kay; Chong, Chia-Yin; Lye, David C B; Lin, Raymond T P; Merits, Andres; Leo, Yee-Sin; et al.
Summary: The reemergence of Zika virus (ZIKV) warrants the need to develop complementary diagnostic measures. In this study, flow cytometry was used to determine the presence of ZIKV NS3 antigen in blood monocytes from ZIKV-infected patients Abstract: Background: Epidemics caused by the reemergence of Zika virus (ZIKV) warrant the need to develop new diagnostic measures to complement currently used detection methods. In this study, we explored the detection of ZIKV antigen in a defined leukocyte subset from patients' whole-blood specimens. Methods: Whole-blood samples were obtained at the acute and early convalescent phases from ZIKV-infected patients during the Singapore outbreak in August–September 2016. Presence of ZIKV antigen was determined by flow cytometry staining for intracellular ZIKV NS3, using a ZIKV-specific polyclonal antibody. The presence of ZIKV antigen was determined in CD45 + CD14 + monocytes. Results: Data showed that ZIKV NS3 antigen could be detected in CD45 + CD14 + monocytes. The levels of detection were further categorized into 3 groups: high (positivity among >40% of monocytes), moderate (positivity among 10%–40%), and low (positivity among <10%). While a majority of patients showed a decrease in the amount of ZIKV antigen detected at later time points, some patients displayed higher levels as the disease progressed. Conclusions: Our data highlights an alternative approach in using flow cytometry as a sensitive method for detecting ZIKV antigen in whole blood. Importantly, it further confirms the role of CD14 + monocytes as an important cellular target for ZIKV infection during the viremic phase.